1994
DOI: 10.3109/00498259409043295
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the cardioprotective agents dexrazoxane (ICRF-187) and levrazoxane (ICRF-186) by the isolated hepatocyte

Abstract: 1. The metabolism of dexrazoxane (ICRF-187) and its optical isomer levrazoxane (ICRF-186) by the isolated rat hepatocyte was studied by hplc. 2. 4-Chlorobenzenesulphonamide, which is a strong inhibitor of dihydropyrimidine amidohydrolase (DHPase), caused 82% inhibition of the loss of dexrazoxane from the hepatocyte suspension. 3. Dexrazoxane was metabolized at an initial rate by isolated hepatocytes that was 1.8 times faster than levrazoxane. This ratio is close to that found for purified DHPase, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…We previously showed in isolated hepatocytes (Hasinoff et al, 1994), in a rat model , and in humans (Schroeder et al, 2003) that dexrazoxane was rapidly metabolized to the one-ring open compounds B and C, and ADR-925 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed in isolated hepatocytes (Hasinoff et al, 1994), in a rat model , and in humans (Schroeder et al, 2003) that dexrazoxane was rapidly metabolized to the one-ring open compounds B and C, and ADR-925 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…ADR-925 may then either remove iron from the iron-doxorubicin complex (Buss and Hasinoff, 1993) (Huang et al, 1982;Diop et al, 2000). Thus, dexrazoxane, which is easily permeable to cells (Dawson, 1975), can be considered a neutral prodrug analog of EDTA.We previously showed in isolated hepatocytes (Hasinoff et al, 1994), in a rat model , and in humans (Schroeder et al, 2003) that dexrazoxane was rapidly metabolized to the one-ring open compounds B and C, and ADR-925 (Fig. 1).…”
mentioning
confidence: 99%
“…We also previously showed that DHPase, which is present in the liver and the kidney, can efficiently hydrolyze dexrazoxane (Hasinoff et al, 1991(Hasinoff et al, , 1994Hasinoff, 1993Hasinoff, , 1994cHasinoff and Aoyama, 1999b) and is likely the enzyme that is primarily responsible for the metabolism of dexrazoxane to B and C. We have also shown that DHPase is unable to convert B and C into ADR-925 (Hasinoff et al, 1991). Likewise, we have shown that DHOase is able to enzymatically hydrolyze B and C to ADR-925 but is unable to hydrolyze dexrazoxane .…”
Section: Discussionmentioning
confidence: 76%
“…It is, however, observed that in both humans and rats , dexrazoxane is quickly metabolized to B and C, and then to ADR-925. The rapid rate of hydrolysis of dexrazoxane to B and C and the rapid appearance of ADR-925 in plasma in vivo suggested that, first, dexrazoxane and, then, B and C were all enzymatically metabolized.We previously showed that the dexrazoxane metabolic intermediates B and C are rapidly formed from dexrazoxane in a primary rat hepatocyte suspension (Hasinoff et al, 1994), a result that is consistent with dexrazoxane being metabolized by the zinc hydrolase DHPase (EC 3.5.2.2). However, although pure DHPase enzymatically hydrolyzes dexrazoxane to B and C, it is unable to enzymatically hydrolyze B and C to ADR-925 (Hasinoff et al, 1991;Hasinoff, 1993).…”
mentioning
confidence: 87%
See 1 more Smart Citation